2019
DOI: 10.1111/fog.12427
|View full text |Cite
|
Sign up to set email alerts
|

Earlier migration and distribution changes of albacore in the Northeast Atlantic

Abstract: Marine species have exhibited trends in their geographic distribution and phenology in recent decades, and these changes are triggered by climate variability or anthropogenic pressures. Northeast Atlantic albacore has recently been identified to show changes of this nature, although the underlying causes are still uncertain. The aim of this work was to analyse the Northeast Atlantic albacore distribution shifts and phenological changes during the trophic migration that juveniles undertake from late spring to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 45 publications
(83 reference statements)
0
7
0
Order By: Relevance
“…Such productivity and diversity, however, might be altered by climate change in the near future, as rising temperatures (0.26 • C per decade; Costoya et al, 2015) are expected to increase ocean stratification and reduce primary production and zooplankton biomass in the area (Chust et al, 2014a). In recent years, losses in fisheries production have already been reported (Free et al, 2019), together with changes in the composition, distribution, and phenology of fish species (Blanchard and Vandermeirsch, 2005;Chust et al, 2019;Baudron et al, 2020). Cetacean spatiotemporal variability, in contrast, has been mainly assessed by exploring changes in their relative abundance (Hemery et al, 2007;Castège et al, 2013;Authier et al, 2018), although both abundance and distribution are considered key criteria by the European Marine Strategy Framework Directive (MSFD; Directive 2008/56/EC) aiming to assess the environmental status of species and ecosystems in European Union waters.…”
Section: Introductionmentioning
confidence: 99%
“…Such productivity and diversity, however, might be altered by climate change in the near future, as rising temperatures (0.26 • C per decade; Costoya et al, 2015) are expected to increase ocean stratification and reduce primary production and zooplankton biomass in the area (Chust et al, 2014a). In recent years, losses in fisheries production have already been reported (Free et al, 2019), together with changes in the composition, distribution, and phenology of fish species (Blanchard and Vandermeirsch, 2005;Chust et al, 2019;Baudron et al, 2020). Cetacean spatiotemporal variability, in contrast, has been mainly assessed by exploring changes in their relative abundance (Hemery et al, 2007;Castège et al, 2013;Authier et al, 2018), although both abundance and distribution are considered key criteria by the European Marine Strategy Framework Directive (MSFD; Directive 2008/56/EC) aiming to assess the environmental status of species and ecosystems in European Union waters.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, fishermen reported albacore “pushing north” during recent warm‐water oceanographic anomalies (Interviews 5, 20), with schools of fish observed off Southeast Alaska (Cavole et al., 2016). A northward shift in fishing opportunities could coincide with future projections of favourable thermal habitat (Christian & Holmes, 2016), but studies conducted in other ocean basins have shown that albacore distributions are highly variable and do not always correspond with shifts in oceanographic habitat (Chust et al., 2019). Though more research is required to determine how interactions between climate, feeding, migration and spawning throughout the range of the species in the North Pacific are likely to mediate fishable biomass, we would suggest asymmetric impacts are likely across the different segments of North American fishing fleets.…”
Section: Discussionmentioning
confidence: 99%
“…In reality, despite the dynamicity of marine fisheries, climatic change, global warming, and various biotic and abiotic factors could alter tuna migration, food availability, catch rate, and stock indices, all of which are related to habitat [45,56,58,60,80]. Determining the precise mechanism(s) underlying suitable habitat is challenging; additionally, whether the interannual distribution shifts of species are mainly associated with other ocean-climate factors, prey abundance, or even another factor like fleet behavior [81] remains unclear. Hence, indirect habitat modeling using diet composition indicators (e.g., small pelagic fish, crustacean, and squid) and historical changes in hotspot habitat resulting from empirical habitat suitability models, such as that of the present study, and advanced modeling of population dynamics [82] could also be suggested as further research areas for the implementation of regional EBFM in the SAO.…”
Section: Discussionmentioning
confidence: 99%